Using employee creativity to unpack the 'black box' in the High-Performance Work System (HPWS)- firm performance nexus - Ismail, Abdussalaam Iyanda; Abdul Majid, Abdul Halim; Ameen, Abdullateef; Raza, Saqlain; Akindele, Iyiola Tomilayo (World Scientific Publishing Europe Ltd., 2020)
The extant research findings have identified lacunas (i.e. gaps, unresolved issues, and black box) in the High-Performance Work System (HPWS)-Performance relationship and suggested usage of a mechanism (mediator) that can close up the identified lacunas. Thus, this study investigates whether employee creativity can play a mediating role in the relationship between HPWS and firm non-financial performance. The sample size of the study is 518, and respondents were selected through stratified sampling technique. Data were collected from the sampled 518 managers in Nigerian